Early performance: courts and audiences shifting paradigms in early English drama studies - Carpenter, Sarah (Routledge, 2021)
"These essays of Sarah Carpenter have been selected to reflect her career's close focus on the relationship of performance and audience. They are drawn from the last 25 years of her writing, and this has enabled the editors to organise them not chronologically but rather to develop her central theme through a range of genres, including morality plays, the interlude, court entertainments, international political spectacle, and the public 'performances' of natural and maintained fools. As a scholar who also has experience of acting and of production, Carpenter is particularly sensitive to the implications of location for creating meaning and generating audience reaction. The essays are focused on a relatively short time-span of 120 years, from the late fifteenth to the turn of the seventeenth century, and thus nuance a period traditionally divided between the late medieval and the early-modern, and between Catholicism and Protestantism. Carpenter shows how the dynamics of theatrical engagement in which the roles of audience and performer are frequently mixed or even reversed offer a more creative route to understanding how the individual and society respond to change"--
Description based on online resource; title from digital title page (viewed on July 30, 2020)
Keywords: English drama / To 1500 / History and criticism; English drama / Early modern and Elizabethan, 1500-1600; Theater / England / History / Medieval, 500-1500; Theater / England / History / To 1500